Swelling-activated chloride currents in embryonic chick heart cells - Wang Hua; Mei Yan-Ai; Wu Ming-Ming; Sun Jia-Ting; Zhou Han-Qing; Zhang Zhi-Hong (Acta Pharmacologica Sinica, 2016)
"AIM: To characterize a swelling-activated chloride current, I(Cl, swell), in white Leghorn chick heart cells and the effects of chlorpromazine (CPZ) effects. METHODS: The patch-clamp technique in the whole-cell configuration was used. RESULTS: Hyposmotic swelling elicited I(Cl, swell) in white Leghorn chick heart cells. The current amplitude increased from (452 +/- 200) pA to (849 +/- 373) pA with a reduction of osmolarity from 300 mmol.L-1 to 270 mmol.L-1, 4',4-Diisothiocyanostilbene-2,2'-disulphonic acid (DIDS) 100 mumol.L-1 decreased I(Cl, swell) from (1196 +/- 505) pA to (830 +/- 328) pA in hyposmotic solution. In white Leghorn chick heart cells I(Cl, swell) was not induced by CPZ 30 mumol.L-1, which is different from the case of E coli spheroplast. CONCLUSION: Swelling-activated chloride current was activated by hyposmotic swelling in white Leghorn chick heart cells. The mechanism for activating the current is different from that of mechanosensitive ion channels of E coli."